Mid- to long-term follow-up of combined small implants: a third-generation patellofemoral arthroplasty associated with a medial or lateral unicompartmental knee arthroplasty. (1st May 2021) - Rossi, Stefano M. P.; Perticarini, Loris; Clocchiatti, Susanna; Ghiara, Matteo; Benazzo, Francesco
Abstract : Aims: In the last decade, interest in partial knee arthroplasties and bicruciate retaining total knee arthroplasties has increased. In addition, patient-related outcomes and functional results such as range of movement and ambulation may be more promising with less invasive procedures such as bicompartmental arthroplasty (BCA). The purpose of this study is to evaluate clinical and radiological outcomes after a third-generation patellofemoral arthroplasty (PFA) combined with a medial or lateral unicompartmental knee arthroplasty (UKA) at mid- to long-term follow-up. Methods: A total of 57 procedures were performed. In 45 cases, a PFA was associated with a medial UKA and, in 12, with a lateral UKA. Patients were followed with validated patient-reported outcome measures (Oxford Knee Score (OKS), EuroQol five-dimension questionnaire (EQ-5D), EuroQoL Visual Analogue Scale (EQ-VAS)), the Knee Society Score (KSS), the Forgotten Joint Score (FJS), and radiological analysis. Results: The mean follow-up was nine years (6 to 13). All scores significantly improved from preoperatively to final follow-up (mean and SD): OKS from 23.2 (8.1) to 42.5 (3.5), EQ-5D from 0.44 (0.25) to 0.815 (0.1), EQ-VAS from 46.7 (24.9) to 89.1 (9.8), KSS (Knee) from 51.4 (8.5) to 94.4 (4.2), and KSS (Function) from 48.7 (5.5) to 88.8 (5.2). The mean FJS at final follow-up was 79.2 (4.2). All failures involved the medial UKA + PFA group. Overall, survival rate was 91.5% for all the combined implants at ten years with 95% confidence intervals and 22 knees at risk. Conclusion: Excellent clinical and radiological outcomes were achieved after a third-generation PFA combined with a medial or lateral UKA. BCA with unlinked partial knee prostheses showed a good survival rate at mid- to long-term follow-up. Cite this article: Bone Joint J  2021;103-B(5):840–845.